2020
DOI: 10.2147/phmt.s266063
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Profile of Covid-19 in Children, Review of Existing Literatures</p>

Abstract: WHO has confirmed that COVID-19 disease is a pandemic on March 11, 2020. The disease is caused by a new virus called SARS-CoV-2. Since, the pandemic was announced around 18,854,287 cases and 708,639 deaths were reported as of August 7, 2020. This review aimed to explore the etiology, pathogenesis, manifestation and complication. The phylogenetic study showed that SARS-CoV-2 is a single-stranded RNA virus. The virus is very contagious and has rapidly spread globally. Its unique structure called S glycoproteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Underlying chronic pulmonary disease, cardiovascular disease, immune-suppression, and obesity significantly contributed to the complications. [29] Based on the clinical presentation, the COVID 19 cases were subdivided into four categories for management purpose. Children having fever and other constitutional symptoms without fast breathing or radiological findings were categorized as mild illness group.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying chronic pulmonary disease, cardiovascular disease, immune-suppression, and obesity significantly contributed to the complications. [29] Based on the clinical presentation, the COVID 19 cases were subdivided into four categories for management purpose. Children having fever and other constitutional symptoms without fast breathing or radiological findings were categorized as mild illness group.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in pulmonary CT have been observed in asymptomatic children or with mild manifestations. In newborn abnormal radiological findings were described in 48% but specific lesions were not as frequent as in older children; 4% had GGO, 20%, unilateral patchy infiltration and 12% bilateral involvement (23).…”
Section: Clinical Manifestationsmentioning
confidence: 92%
“…The chest X ray in children was abnormal up to 49.1% even some of them being asymptomatic (23). Pulmonary involvement in CT scan described by Simoni et al in a systematic review, which brought together 166 children, showed mostly bilateral infiltration, between 57 and 75%, and a peripheral distribution between 12.5 and 51.7% (24).…”
Section: Clinical Manifestationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have also elucidated the slightly higher incidence of COVID-19 in male children and increased susceptibility of infants to severe disease. 1,4 In a meta-analysis of 31 studies in hospitalized children, a cumulative mortality rate of 1.1% was reported. 5 The relatively higher rate of mortality in our study is partly due to the younger population; but other contributing factors, for which our dataset may not account for, need further and thorough investigation.…”
mentioning
confidence: 99%